PENGARUH GREEN ACCOUNTING DAN KEPEMILIKAN SAHAM PUBLIK TERHADAP KINERJA KEUANGAN DENGAN PENGUNGKAPAN CSR SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN SEKTOR INDUSTRI DASAR DAN KIMIA YANG TERDAFTAR DI BEI TAHUN 2015-2019 - Ika Widya Rahmadhani; Dwi Suhartini; Astrini Aning Widoretno (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2021)
This study was conducted to examine and analyze the effect of green accounting and public share ownership on financial performance through CSR disclosure in basic and chemical industry companies in 2015-2019. The population in this study amounted to 79 companies listed on the Indonesia Stock Exchange. This study uses secondary data in the form of annual reports and sustainability reports of companies in the basic and chemical industry sectors. The sampling technique used purposive sampling technique and data analysis using SEM PLS with WarpPLS 7.0 software. The results of this study indicate that green accounting has no effect on financial performance, while public share ownership and CSR disclosure have an effect on financial performance. Green accounting and public share ownership do not affect CSR disclosure, then green accounting and public share ownership do not affect financial performance indirectly through CSR disclosure.